2011
DOI: 10.1111/j.1551-2916.2010.04295.x
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundaries in Uranium Dioxide: Scanning Electron Microscopy Experiments and Atomistic Simulations

Abstract: The distribution and atomic structure of grain boundaries has been investigated in UO2. Our scanning electron microscopic/electron backscatter diffraction experiments on a depleted UO2 sample showed real nuclear fuels contain a combination of special coincident site lattice (CSL) and general boundaries. The experimental data indicated that ∼16% of the boundaries were CSL boundaries and the CSL distribution was dominated by low Σ boundaries; namely Σ9, Σ3, and Σ5 Based on our experimental observations, the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 33 publications
4
73
0
Order By: Relevance
“…UO 2 , is the P 9, having a symmetry angle [16] of 38.94°; however, this has also been determined in materials with significantly larger grain sizes. Moreover, as mentioned above, it is not possible to use techniques such as EBSD or OIM to determine the CSL values in such fine-grained materials as those in this study.…”
Section: Grain Growth and Grain Boundary Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…UO 2 , is the P 9, having a symmetry angle [16] of 38.94°; however, this has also been determined in materials with significantly larger grain sizes. Moreover, as mentioned above, it is not possible to use techniques such as EBSD or OIM to determine the CSL values in such fine-grained materials as those in this study.…”
Section: Grain Growth and Grain Boundary Evolutionmentioning
confidence: 99%
“…As such, it may only be speculated that the dominant CSL is that of the P 9 in this study. Previous studies of the grain boundaries in UO 2 [16,17] have shown that Schottky defects exist at the high-misorientation (asymmetric) grain boundaries, helping to stabilize the system by reducing the energy at the grain boundary. The lower angle grain boundaries and CSL (symmetric) grain boundaries are stabilized by dislocations terminating at the grain boundaries [16,17].…”
Section: Grain Growth and Grain Boundary Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the pinning of dislocations by implanted helium in aluminum 8 or niobium 9 shows the importance of segregation in determining both enhanced diffusion of atomic species and changes in mechanical properties of the bulk material. Metal-ceramic interfaces, which can be composed of ordered arrays of dislocations, have also been shown to act as energetically favorable nucleation points.…”
mentioning
confidence: 99%
“…For details, see Technical Spotlight on page 9. [INL] Work continued on development of a method to account for fuel cracking in engineering-scale analyses by calibrating the cohesive zone model for the fracture of UO 2 …”
Section: Pin-scale Code Developmentmentioning
confidence: 99%